EFFECT OF DRIP IRRIGATION AND MULCHES ON GROWTH AND YIELD OF BELL PEPPER (CAPSICUM FRUITESENS L.) - KUMARI, P.V.L RATNA; PRASADIN, P. PRABHU; RAO, M. SINGA; SHIVSHANKAR, M. (Annals of Agricultural Research, 2014)
A field study was conducted on a gravelly sandy loam soil in the Agricultural College Farm, Rajendranagar, Hyderabad, Andhra Pradesh, India during rabi 2001-02 to study the effect of drip irrigation at three levels of water application i.e., at 1.0, 0.8 and 0.6 of maximum evapotranspiration and surface irrigation in combination with two mulches viz., black polythene and paddy husk on growth and yield of bell pepper. For surface irrigation, 40 mm depth of water was given at IW/CPE ratio of 1.00. Plants irrigated through drip on an average were taller at harvest by about 5.5 cm compared to those received surface irrigation. Plant height was more in black polythene mulch (47.3 cm) followed by paddy husk (42.3) and was least in unmulched (35.6) plots. The average dry matter produced was higher in drip irrigation treatments compared to surface irrigation throughout the growth period. It was highest in black polythene mulch followed by paddy huxk and was lowest in unmulched plots throughout the crop growth period. drip irrigation, in general, recorded significantly higher green fruit yield compared to surface irrigation. Among the irrigation treatments, highest yield was recorded in drip 1.0 followed by drip 0.8 and drip 0.6 which were statistically at par. Black polythene mulch was found to be superior (9.6 t ha-1) to paddy husk mulch (8.68 t ha-1) and no mulch (7.88 t ha-1) treatments. Among all the treatments, highest yield was obtained with drip 0.8 and black polythene mulch combination and lowest was recorded in surface irrigation without mulch. The use of drip either alone or in combinaation with mulching was better over surface irrigation.